Supporting images for the paper: Supercomplex organization of the electron transfer system in marine bivalves, a model of extreme longevity - Enrique Rodriguez; Pierre U. Blier; Tory M. Hagen (2021)
Original gels used for figure 1 of the JGBS paper, and for proteomics analysis. The leftmost well is the marker, and species are ranked from short to longest-lived